Ligand recognition and signal transduction by lectin receptor-like kinases in plant immunity - Liu, Lu; Liu, Jun; Xu, Ning (Frontiers in Plant Science, 2023)
Lectin receptor-like kinases (LecRKs) locate on the cell membrane and play diverse roles in perceiving environmental factors in higher plants. Studies have demonstrated that LecRKs are involved in plant development and response to abiotic and biotic stresses. In this review, we summarize the identified ligands of LecRKs in Arabidopsis, including extracellular purine (eATP), extracellular pyridine (eNAD+), extracellular NAD+ phosphate (eNADP+) and extracellular fatty acids (such as 3-hydroxydecanoic acid). We also discussed the posttranslational modification of these receptors in plant innate immunity and the perspectives of future research on plant LecRKs.